2012
DOI: 10.1503/jpn.110107
|View full text |Cite
|
Sign up to set email alerts
|

Ionotropic glutamate receptor mRNA editing in the prefrontal cortex: no alterations in schizophrenia or bipolar disorder

Abstract: IntroductionGlutamate is the main neurotransmitter responsible for excitatory neurotransmission throughout the brain. Glutamate serves as a ligand for G-protein coupled metabotropic and ionotropic (iGluRs) receptors. The latter consists of N-methyl-D-aspartate, α-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) and kainate (KA) subtypes. Glutamate dysfunction has been linked to numerous diseases, including schizophrenia, bipolar disorder and major depressive disorder. 1-6The AMPA and KA receptors are liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…Lyddon and colleagues examined the RNA editing in AMPA/kainate receptors in the same samples (i.e., the Neuropathology Consortium samples) [ 17 ]. Their finding that the flop isoform of GRIA3 and GRIA4 showed higher R/G site editing compared with the flip isoform was replicated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lyddon and colleagues examined the RNA editing in AMPA/kainate receptors in the same samples (i.e., the Neuropathology Consortium samples) [ 17 ]. Their finding that the flop isoform of GRIA3 and GRIA4 showed higher R/G site editing compared with the flip isoform was replicated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies regarding the RNA editing of AMPA/kainate receptors is relatively small. While several studies showed no alteration in schizophrenia [ 16 , 17 ] and bipolar disorder [ 17 ], a recent study revealed altered editing of the I/V site of GRIK2 in bipolar disorder [ 6 ]. The role of RNA editing of glutamate receptors has drawn attention because the glutamatergic hypothesis of mood disorders has recently been established [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of such a difference after administration of an AMPA receptor antagonist suggested that this was related to altered function of glutamate receptors. 77 Another study showed no difference in RNA editing of glutamate receptors in BD, 78 whereas reduced editing of AMPA receptors was found in schizophrenia. 79…”
Section: Rna Editingmentioning
confidence: 99%
“…Each gene can yield several splice variants, which may form channels with different kinetics. Additionally, GluA2 mRNAs editing allows further changes in channel properties [91].…”
Section: The Ampa Receptor Auxiliary Subunitsmentioning
confidence: 99%